Analysis of Students’ Mathematical Literacy through Minimum Competency Assessment (AKM)-Based Questions on Arithmetic Sequence - Isna Cholifah; Nella Haiprilisya; Choerunnisa; Shafwa Maitsa Adzra Tsani; Firda Pujiana; Neneng Aminah; Dede Endang Mascita (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Indonesia's 2022 PISA results have declined compared to 2018, raising concerns about educational quality globally. National assessments focusing on mathematical literacy, utilizing Minimum Competency Assessment (AKM) questions, have become commonplace for students. This study aimed to investigate students' mathematical literacy skills through AKM-based questions on arithmetic sequence patterns. Employing a qualitative approach with 10th-grade students, data collection involved written tests, followed by data reduction, presentation, and conclusion drawing. Results indicate that 42.86% (12 students) demonstrated high mathematical literacy, reflecting adequate problem-solving skills. However, 35.71% (10 students) scored low, revealing significant challenges in conceptual understanding and application. These findings emphasize the need for targeted interventions to enhance mathematical literacy, particularly in contextual problem-solving and mathematical concept application.